The impact of value-added taxes and inflation threshold on economic growth in the Kingdom of Saudi Arabia - Louail, Bilal; Waked, Sami Sobhi; Riache, Siham (The Economics and Finance Letters, 2024)
The paper contributes to the literature by examining the effects of inflation on economic growth in Saudi Arabia between 2010Q1 and 2022Q4 and exploring whether the VAT impacted the inflation-growth nexus. The literature on the determinants of economic growth has expanded during the last few decades. The impact of inflation on economic growth has received much attention, with contradictory findings. The study employs the Logistic Smooth Transition Regression (LSTR) model to determine the optimal inflation rate and estimate the repercussions of inflation in each regime. The findings show that the optimal inflation rate is 2.47%. Inflation is demonstrated to improve growth if it remains below 2.47%. Nevertheless, as the inflation rate is beyond this threshold, the effect becomes negative. Subsequently, the study accounts for the influence of Value- Added Tax on the link between inflation and growth. According to the empirical estimation, the threshold level of the inflation rate is determined to be 2.88%. In addition, the adverse implications of inflation on growth are higher when we consider the implementation of VAT. Therefore, the study concludes that there are nonlinear effects of the inflation rate on economic growth in Saudi Arabia. The empirical results of the study have important policy implications for Saudi Arabia.